2004
DOI: 10.1590/s0034-89102004000300010
|View full text |Cite
|
Sign up to set email alerts
|

Amputações de extremidades inferiores por diabetes mellitus: estudo caso-controle

Abstract: Objective Lower extremity amputation is an increasing problem among diabetic patients and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
47

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 8 publications
0
16
0
47
Order By: Relevance
“…This result was a positive one, since there is evidence suggesting that tobacco use is associated with the occurrence of amputations. (6,7) As for blood glucose self-monitoring, this is a fundamental measure of diabetes control. (20) In the present study, this activity scored a mean of five on the questionnaire, considered close to the desirable, which is seven.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result was a positive one, since there is evidence suggesting that tobacco use is associated with the occurrence of amputations. (6,7) As for blood glucose self-monitoring, this is a fundamental measure of diabetes control. (20) In the present study, this activity scored a mean of five on the questionnaire, considered close to the desirable, which is seven.…”
Section: Discussionmentioning
confidence: 99%
“…(4,5) Among the chronic complications of diabetes, diabetic neuropathy, which is present in 50% of patients over 60 years of age, is the most important factor in the origin of structural and functional changes in the feet, producing ulcers in the lower limbs. (6,7) A study conducted in a specialized service with patients with diabetes mellitus showed that over 50% of the study population had dermatological conditions conducive to the development of ulcers/lesions. (8) In general, patients with diabetes mellitus recognize the importance of foot care to avoid complications; however, self-care is not performed correctly.…”
Section: Introductionmentioning
confidence: 99%
“…Low education levels can enhance nonadherence to the therapeutic plan though, due to difficulties to read and understand the prescription, thus increasing health risks. Besides, low education levels can limit information access, probably due to compromised reading, writing and speaking skills, as well as the understanding of the disease and treatment's complex mechanisms (14,15) .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with low education have more difficult access to information and find it harder to understand the complex disease mechanisms and treatments provided, thus limiting their opportunities for gaining knowledge about health care (20)(21) . As for family income, the majority (72.7%) had up to five MMWs from retirement plans or diabetic elderly allowance.…”
Section: Acta Paul Enfermmentioning
confidence: 99%